Japanese Vocabulary - Uo, Sumiko (Boca Raton, FL : Barcharts, 2005)
The most frequently used Japanese vocabulary words in a 6-page guide.
CSE
Keywords: Japanese language -- Vocabulary; Japanese language -- Conversation and phrase books -- English; Japanese language -- Grammar; Glossaries, vocabularies, etc